Social withdrawal: An initially adaptive behavior that becomes maladaptive when expressed excessively. (September 2020) - Ike, Kevin G.O.; de Boer, Sietse F.; Buwalda, Bauke; Kas, Martien J.H.
Highlights: Social withdrawal is an adaptive response, but will become maladaptive when chronic. The brain's social decision-making network is a main driver of social approach and avoidance behaviour. Studying social withdrawal requires innovative tools to assess social group dynamics. Building relationships between 'social' genes and neural networks associated to social functioning can be initiated. Abstract: Social withdrawal is found across neuropsychiatric disorders and in numerous animal species under various conditions. It has substantial impact on the quality of life in patients suffering from neuropsychiatric disorders. Often it occurs prodromal to the disease, suggesting that it is either an early biomarker or central to its etiology. Healthy social functioning is supported by the social brain of which the building blocks go back millions of years, showing overlap between humans, rodents and insects. Thus, to elucidate social withdrawal, we have to approach its environmental triggers and its neural and molecular genetic determinants in an evolutionary context. Pathological social withdrawal may originate from a faulty regulation of specific neural circuits. As there is considerable heritability in social disorders, the genetic building blocks of the social decision making network might be our most relevant target to obtain an understanding of the transition of normal social interaction into social withdrawal.